Survey Based Comparative Analysis for Quality Assessment in Public and Private Transportation Services using SERVQUAL Model - Dr. Rajendra R. Chaudhari,; Sunil R. Kewate,; M. S. Satpute,; Dr. Vivek R. Gandhewar, (International Journal of Scientific Research in Science and Technology, 2024)
Public authorities, transport agencies and private operators need to work together to continuously improve the performance of public transport. Any transportation company must use a systemic survey-based approach that critically analyses client requirements in order to assess its success. Using the SERVQUAL model, an effort is made to gain a better knowledge of passenger attitude and satisfaction with the services offered by the public bus transportation system (MSRTC) and private sector is presented. Furthermore, the integrated framework of this study can enhance public transport performance and give customer satisfaction. For the present study purpose, descriptive research has been designed to fulfill the objectives with data collection from different sources and to know customers satisfaction from the services given by Maharashtra State Road Transport Corporation. The questions are developed as to get responses specific to objectives that are proposed to fulfill. For the purpose of the analysis, primary data was collected directly from the passengers. The collected primary data was analysed by percentage method. Broadly we had relied on two sources of information for the present study that is primary and secondary sources of information. Consequently, we relied mostly on research papers and study articles published in the various journals and information available on the internet. Secondary data has been collected from the many administrative officers of MSRTC. This information has been classified by using various techniques of analysis. Primary data has been collected with the help of structured questionnaire for passengers. The main purpose of these questionnaires was to get feedback about services provided by MSRTC. In brief, for the study purpose, survey method was used for the collection of primary data with the help of a questionnaire. The questionnaire was administered to the individual of the selected sample and their responses about themselves have been recorded. The questions were made under nominal and ordinal scales also we used a structured and a non-disguise questionnaire. Before giving out the survey to customers, we conducted a pilot test of 150 surveys, testing to see how it went and allowed it to run for two weeks. The reason for this was to see how easy it was for the respondents to answer the questions in the survey. The results of this turned out to be that most of the customers in Amravati region could easily answer. A comparative analysis is done between MSRTC and private bus transport services. The analysis is done by based on three key parameters and each parameter has three specific facilities in them.
Keywords: Survey questionnaires; SERVQUAL model; Responses; Key parameters; Public and Private